Selecting Evidence-Based Practices: What Works for Me. (May 2019) - Leko, Melinda M.; Roberts, Carly; Peyton, David; Pua, Daisy
As the special education research community continues to identify new evidence-based practices (EBP), educators will need to make choices regarding which EBPs to implement. This article provides educators with practical guidelines for selecting EBPs that will improve outcomes for students with learning disabilities (LD), emotional and behavior disorders (EBD), and autism spectrum disorder (ASD). Among the factors for EBP consideration discussed are strength of evidence, cost, complexity and transferability, and contextual fit. By taking these factors (and others) into consideration, educators can make more informed decisions from the outset about which EBPs will work in their particular contexts, meet the specific needs of their students, and lead to long-term sustainability.